Endoscopic ultrasound guided fine‐needle aspiration: What variables influence diagnostic yield?. Issue 4 (27th December 2017) - Mohanty, Sambit K.; Pradhan, Dinesh; Sharma, Shivani; Sharma, Anurag; Patnaik, Niharika; Feuerman, Martin; Bonasara, Robert; Boyd, Adrienne; Friedel, David; Stavropoulos, Stavros; Gupta, Mala
Abstract : Background: Endoscopic ultrasound (EUS) guided fine‐needle aspiration (FNA) plays an important role in the diagnosis of various lesions. We sought to determine factors that influence the diagnostic yield of EUS–FNA, specifically, the presence of a cytopathologist, FNA site, and the endoscopist's skill. Methods: The data on cytopathologist's availability, duration of procedure, number of passes made, and diagnostic material for cell block (CB) preparation was collected over an 18 months period. Results: 230 specimens (218 patients) were obtained from pancreas (114), lymph node (64), submucosal lesions of the gastrointestinal tract (27), liver (8), and miscellaneous (17) sites. The results were classified as informative (77.8%) and non‐informative (NI) (22.2%). The NI rate was significantly high, when a cytopathologist was absent ( P  = .0008). As the likelihood of cytopathologist's presence increased from 35.8% to 82.9%, the CB quality increased ( P  < .0001). In the absence of a cytopathologist, the likelihood of NI result increased more than 2‐fold ( P  = .03) and of an inadequate CB increased 3‐fold ( P  < .0001). The more experienced endoscopist "C" (compared to the less experienced "A + B") was less likely to get inadequate material (40.5% vs. 66.3%) ( P  = .0001). Conclusion: The diagnostic yield of EUS–FNA is significantly related to the presence of an on‐site cytopathologist and endoscopist's skill in procuring diagnostic material.